Preparation and Application of Class A1 Flame Retardant Composite Material with Waterproof Properties. Issue 8 (3rd August 2022) - Wang, Jialing; Gu, Xinxin; Zhang, Lu; Shang, Xinyue; Kandawa-Schulz, Martha; Song, Wei; Wang, Yihong
ABSTRACT: The Class A1 flame retardant eco-material with excellent comprehensive properties is strongly needed to replace the low-level flame retardant products for potential applications in the building industry. In this work, modified titanium sol with the re-dispersible latex powder (VAE) is compounded to prepare non-combustible flame retardant composites. The optimal content of polylactic acid (PLA) is determined as 10 wt%. The results reveal that the addition of modified titanium sol has simultaneous improvements in flame resistance, water resistance, and mechanical properties of the composite material. The composites with 8 wt% modified titanium sol show low gross heat of combustion (0.646 MJ·kg −1 ) and low water absorption (4.26%), satisfying the enterprise standards. Besides, the flexural strength of the composites exhibited the maximum at 18.8 MPa. Structure observation discloses that the modified titanium sol promotes the formation of a three-dimensional network structure in the material and further forms a dense protective layer during combustion to inhibit burning. Overall results suggest that the composites with modified titanium sol as the Class A1 flame retardant composite will shed light on their promising applications in the construction industry. GRAPHICAL ABSTRACT: uf0001